Harga Murabahah Perspektif Fikih dan Keuangan Islam - Amin Wahyudi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2011)
Murabahah is a unique pattern of business. One side of Murabahah is sale and buy, and the other is debt and credit. Therefore the price of Murabahah contains provisions that differ from regular trading. The price of Murabahah consist of acquisition and mark up. Acquisition price is analyzed based on purchased and all fees that have been made to hold commodities ready for buyer. While the mark up of Murabahah is business advantage. Mark up can be analyzed based on costs, market prices, inflation, risk, and other factors that are not based on interest and usury. The level of mark up depends on the decisions between buyer and seller according to the mechanism of transaction that meet shari’ah principle.